Urdu ka guldasta Gule Lala - Faizia Ehsan Farooqi (Karachi: Oxford University Press., 2022)
**Abstract of *Urdu Ka Guldasta Gule Lala*** Urdu Ka Guldasta Gule Lala* is a thoughtfully curated Urdu language textbook, featuring a diverse collection of prose, poetry, and stories aimed at enhancing students' linguistic and literary skills. The book provides exercises that focus on improving reading comprehension, grammar, and writing techniques, while fostering creativity and critical thinking. Through its rich selection of classical and modern works, students are introduced to the beauty and depth of Urdu literature. The book also encourages a deeper understanding of the cultural and historical context of the texts, making it a comprehensive resource for developing a strong foundation in Urdu.